(untitled) (Journal of Contemporary Educational Policies and Practices, 2023)
Teachers’ planning as a research area still receives little attention. This study focuses on developing a research-informed framework to assess teachers’ statistics lesson plans. Using a design-based research approach, we developed a framework that includes (a) two criteria related to learning intentions (clear and comprehensive), (b) four criteria related to task features (statistical literacy, statistical investigation, real data, multiple representations), and (c) one related to constructivist lessons. Then, the team provided professional development on statistical literacy and ways to elicit and develop it in the classroom. After that, the teachers discussed the framework and used it to revise their lesson plans. Also, teachers provided feedback to revise the framework. We discuss how the framework can offer a tool for researchers to examine teacher planning competence and teachers to reflect on their practice.